2022
DOI: 10.3390/tomography8040137
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis of the Heart: A Diagnostic Challenge

Abstract: Tuberculosis of the heart is relatively rare and presents a significant diagnostic difficulty for physicians. It is the leading cause of death from infectious illness. It is one of the top 10 leading causes of death worldwide, with a disproportionate impact in low- and middle-income nations. The radiologist plays a pivotal role as CMR is a non-invasive radiological method that can aid in identifying potential overlap and differential diagnosis between tuberculosis, mass lesions, pericarditis, and myocarditis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…The clinical presentation of TM varies but is generally associated with the disease severity and affected site, ranging from asymptomatic, pericarditis, arrhythmias, valve dysfunction, ventricular outflow tract obstruction, and impaired myocardial contractility to heart failure ( 17 ). Prior to death from TM, most patients have no relevant medical history and are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical presentation of TM varies but is generally associated with the disease severity and affected site, ranging from asymptomatic, pericarditis, arrhythmias, valve dysfunction, ventricular outflow tract obstruction, and impaired myocardial contractility to heart failure ( 17 ). Prior to death from TM, most patients have no relevant medical history and are asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we analyzed myocardial TB-related sudden deaths since 1970 ( Table 1 ) and found that, of the 12 cases identified, 4 were positive for acid-fast bacilli staining, 6 were negative, and the remaining were not tested using ZN staining of myocardial tissue. Studies have shown that the PCR method has 96%–100% specificity for detecting Mycobacterium TB in pericardial fluid; however, some reports have shown that it has only 15%–20% sensitivity ( 17 ). du Toit-Prinsloo and Saayman described TM confirmed by histomorphology despite PCR results being negative ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pericardial enhancement become more irregular in chronic pericarditis. 16 (2) CCP: CCP is characterized by a thickened, fibrotic, rigid, and adherent pericardium which restricts diastolic filling and lead to diastolic dysfunction of ventricles and potential symptoms of right heart failure. MRI has a reported accuracy of 93% for differentiation between CP and RCMP on the basis of depiction of thickened pericardium (> 4 mm).…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…First case of myocardial TB was reported by Maurocordat on autopsy in 1664. 16 Myocardial involvement in TB is rare, documented in up to 0.3% of individuals dying due to tuberculsosis, 24 often not diagnosed while they are alive. 25 The tuberculous myocarditis cases were predominantly seen with concomitant pulmonary infection (56%) and concomitant pericarditis (43%).…”
Section: Myocardial Involvementmentioning
confidence: 99%
“… 7 , 8 However, adverse events can be reduced with effective treatment, which is dependent on accurate diagnosis, which is still quite difficult in TBP. 9 In early pericarditis with massive pericardial effusion, pericardial puncture can be performed to obtain a pericardial fluid specimen for adenosine deaminase (ADA) and other related tests. 10 However, positive ADA test is not microbiological evidence, and septic infection or tumor can cause ADA levels to rise in the fluid, thereby leading to a misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%